Application of Remote Patient Monitoring Technology in Medical Rehabilitation Programs - Mikhail A. Eremushkin; Tatyana A. Knyazeva; Elena V. Malakhova; Olga G. Makarova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
AIM. To develop an original information technology for remote monitoring and to conduct a scientific justification for its use for monitoring and evaluating the motor regimen and the main physiological parameters of patients in a rehabilitation center. MATERIAL AND METHODS. The original architecture of the software and hardware complex was used (certificate of state registration of the computer program No. 2022611766 of February 1, 2022), allowing to the attending physician's PC and wearable devices (smart watches) of the patient with the function of the 24-hour registration of motor activity and heart rate indicators of users. The study involved 21 patients, who underwent medical rehabilitation courses in a round-the-clock hospital. 11 patients underwent cardiorehabilitation programs for the diagnosis of chronic coronary heart disease, myocardial infarction in the past (I25.2 according to ICD-10); 10 patients due to a condition after COVID-19 (U09.9 according to ICD-10). RESULTS AND DISCUSSION. When comparing the motor characteristics of the 2 study groups, it was found that the average number of steps per day was 9004.6 in the group of patients with a diagnosis of I25.2, which equals the distance of 6.6±2.63 km, and 10072.4 steps per day and 7.45±3.12 km in the group with a diagnosis of U09.9, respectively (p<0.001). In both groups, during the course of medical rehabilitation, as a rule, 3 peaks of an increase in motor load were observed - on days 2-3, 5-6 and 8. The period of physical activity in group I25.2 averaged 5:45±0:33 hours, and in group U09.9 - 5:30±0:23 hours. The total density of motor load in both groups corresponded to ≈ 35-36%. However, the average time of motor load spent on active physical rehabilitation procedures in the group with a diagnosis of I25.2 was 1:45±0:17 hours, and in the group U09.9 only 1:05±0:14 (p<0.01). In this connection, the motor density of the motor load of rehabilitation measures in the groups corresponded to 26.6% and 19.8%. CONCLUSION. The software package for remote monitoring of the motor regime and the main physiological parameters of patients has demonstrated the possibility of its use in medical practice, namely for patients at the 2nd stage of medical rehabilitation in a round-the-clock hospital and can be recommended for inclusion in programs of spa treatment.